Research on sports reform in the network era based on educational psychology in the context of the COVID-19 - Fan, QI (Frontiers in Psychology, 2023)
In the context of the continuous progress of the “Internet+” era and the exceptionally severe outbreak of the Covid-19, online education confronts many challenges and also brings unlimited development opportunities. In this paper, taking six universities with sports majors in Chongqing as the research objects, we analyze the current situation and problems of the development and construction of online education resources for sports in colleges and universities by browsing the official websites of colleges and universities, investigating the cooperation between colleges and universities and Massive Open Online Course (MOOC), and conducting a questionnaire survey on students. Specifically, we investigated students’ online learning habits, their experience of using online education platform and the difficulties they encountered in the process, based on which two issues were raised: learning needs and learning experience. The results show that it is necessary to innovate the traditional inefficient classroom teaching model based on the values of adapting to the characteristics of the “Internet+” era and learning advanced teaching rules, thus optimizing teaching effectiveness and fostering students’ independent learning, thinking and innovation.